К 100-летию со дня рождения С.Н. Бибикова. Штрихи к портрету: взгляд в прошлое - Мыц, В.Л. (Археологический альманах, 2009)
This paper is analyzing the life way and scientific achievements of the outstanding pre-historic archaeologist Sergei Nikolaevich Bibikov (1908-1988). His scientific career started in the mid of 20-th. Bibikov participated in Ernst and Bonch-Osmolovski excavations of Crimean Palaeolithic rock-shelters. In 1941 Bibikov defended PhD thesis: “The Late Palaeolithic settlements in Shan Koba and Murzak Koba rock-shelters”. In 1953 Bibikov defended the habilitation thesis: “The Early Tripole settlement Luka Vrublevetskaya on Dniester River”. Bibikov is the author of numerous articles and monographs. At the end of 60-th he proposed new, as for the Soviet pre-history, approaches for the interpretation of archaeological material: paleo-economy and paleo-demography.